2022
DOI: 10.2183/pjab.98.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular physiology regulating cold tolerance and acclimation of <i>Caenorhabditis elegans</i>

Abstract: Many organisms can survive and proliferate in changing environmental temperatures. Here, we introduce a molecular physiological mechanism for cold tolerance and acclimation of the nematode Caenorhabditis elegans on the basis of previous reports and a new result. Three types of thermosensory neurons located in the head, ASJ, ASG, and ADL, regulate cold tolerance and acclimation. In ASJ, components of the light-signaling pathway are involved in thermosensation. In ASG, mechanoreceptor DEG-1 acts as thermorecepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…C. elegans possesses cold tolerance, depending on the cultivation temperature ( Fig. 1 A and B ) ( 3 – 7 ). Moreover, temperature acclimation, a phenomenon in which animals acclimate to a new temperature in a few hours, has been observed ( 4 , 5 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C. elegans possesses cold tolerance, depending on the cultivation temperature ( Fig. 1 A and B ) ( 3 – 7 ). Moreover, temperature acclimation, a phenomenon in which animals acclimate to a new temperature in a few hours, has been observed ( 4 , 5 ).…”
mentioning
confidence: 99%
“…1 A and B ) ( 3 – 7 ). Moreover, temperature acclimation, a phenomenon in which animals acclimate to a new temperature in a few hours, has been observed ( 4 , 5 ). Our previous studies reported that ASJ thermosensory neurons respond to thermal stimuli via the cyclic guanosine monophosphate (cGMP)-gated channels TAX-2/TAX-4 ( 3 ).…”
mentioning
confidence: 99%
“…In animals cultivated at 15°C, the mutants of the DEG/ENaC-type mechanoreceptor DEG-1 and xanthine dehydrogenase XDH-1 exhibited an abnormal decrease in cold tolerance. In the sensory neuron ASG, DEG-1 receives temperature information and transmits it to the interneurons AVH and AIN, wherein XDH-1 acts as a modulator of the neuronal activity of AVH and AIN 26,27 . Under 15°C cultivation condition, the epistasis analysis indicated that CPT affects cold tolerance downstream of DEG-1 and XDH-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the impact of chemical substances on tissues, we examined the drug effect in various mutants defective in genes that regulate cold tolerance or cold acclimation. XDH-1 encoding xanthine dehydrogenase controls cold tolerance by regulating the response to temperature in AIN and AVH 26,27 . Although wild-type animals cultivated at 15°C could survive at 2°C for 48 h, xdh-1 mutant control animals could not survive at 2°C (Fig.…”
Section: Cpt and Lmb Affect Temperature Signaling Pathways In Asgmentioning
confidence: 99%
See 1 more Smart Citation